Horizontally deplacement geomasses in the continental rift geostruсtures (on the example of the Dnipro-Donets paleorift). Part 2. Structural parageneses of the reid deformation of the sedimentary cover - Бартащук, Олексій Вацлавович; Суярко, Василь Григорович (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Formulation of the problem. The inversion stages of the structural-material evolution of the continental crust are characterized by regional scale of the deformation of volume tectonic flow of platform sedimentary rocks, which caused significant horizontally-healthy movements of tectonically activated geo-mass in the intra-plate graben-rift. The dynamic deformation of geomases manifests itself at the final stages of the geological development of such structures; therefore, it determines the main features of the systemic organization of the modern architecture of the basement and sedimentary cover complexes.Review of previous publications and studies. Secondary deformation linear slope, according to Patalakha E. (1979); Alekseev V. (1990) is considered as a set of local strike-slip zones, formed on spherically-located viscous faults, forming joint tectonic flows. The structural skeleton of tectonic flows, as the basis of the tectonic dislocation process, make offsets with the horizontally and rotational component movements. Horizontal landslides are typical disjunctive elements of the continental structures formed in the geodynamic conditions of the transtension (grabens, rifts), transpression (folded mobile belts, intra-plate activation zones), as well as the basic structural elements of the strike-slip tectonics of the sedimentary basin.The purpose of the article. The second part of the trilogy continues regional geotectonic studies of post-rift complications of the sedimentary cover structure of Dnipro-Donets Paleorift (DDP), covering the three main stages of the platform tectonic activation. Late Hercynian epoch was characterized by the formation of large linear anticlinal zones and salt-shafts against the background of the general syneclizal deflection of sedimentary basin, located within the paleorift. Cimmerian epoch of tectonic activity led to significant thrust deformations of the primary structural forms of the cover in the geodynamic setting of collision compression with intensification of the horizons of the sedimentary cover. The structural manifestation of strike-slip tectonics at Alpine epoch in sedimentary complexes are mainly horizontal displacements of geomases of blocks, lineaments, local tectonic elements and structures along dynamically interconnected coulisse of strike-slip domains.Methods. Structural kinematic analysis of transformations of the fracture systems of the Upper-Visean sedimentary complex under the influence of natural mechanism of reid tectonic flow of rocks.Results. The secondary structures of strike-slip deformation, structural kinematic parageneses, dislocations zones and subregional structural waves were identified in the structure of the platform cover, which are natural geological objects formed at the inversion stages of geological development of DDP.Scientific novelty and practical significance. The result of structural manifestation of volume tectonic flow in the platform complex was horizontal displacements of the original tectonic elements, blocks, segments, structures along dynamically-linked strike-slip domains. This is caused by the formation of secondary deformation structures of various scales, morphology and genesis, which comprise longitudinal structural waves of strips of post-rift deformations in the structure of the sedimentary cover of DDP.